A review of the Australian millipede genus Atelomastix (Diplopoda: Spirostreptida: Iulomorphidae) - Edward, Karen L.; Harvey, Mark S. (Zootaxa, 2010)
A review of the Australian endemic millipede genus Atelomastix reveals the presence of 28 species, including the type species A. albanyensis Attems, A. nigrescens Attems, and 25 new species from Western Australia, as well as A. solitaria Jeekel from Victoria. All species are from the high rainfall zone of southern Australia. The new species are: A. anancita, A. attemsi, A. bamfordi, A. brennani, A. culleni, A. danksi, A. dendritica, A. ellenae, A. flavognatha, A. francesae, A. gibsoni, A. grandis, A. julianneae, A. lengae, A. longbottomi, A. mainae, A. melindae, A. montana, A. poustiei, A. priona, A. psittacina, A. rubricephala, A. sarahae, A. tigrina and A. tumula. Most species are shown to have extremely small distributions and all are classified as short-range endemic species. Most species have been collected at very few locations, occurring in discontinuous habitats such as mountain ranges, islands, granite outcrops, or fragments of wet forest.